COMPARATIVE STUDY ON EFFICACY OF AMOXICILLIN WITH CLAVULANIC ACID VERSUS AZITHROMYCIN IN TONSILLITIS - Shrestha, Ruchi; Karki, Sirisa; Manandhar, Tejendra; Deo, Sushma (Journal of Universal College of Medical Sciences, 2018)
Introduction: Tonsillitis is the most commonly encountered health related problems in the general population. Good hydration, use of analgesic along with antibiotics is important for treatment. Penicillin was recommended as the first line treatment for bacterial tonsillitis but now has been replaced mostly by newer antibiotics. This study was attempted to compare the efficacy of amoxicillin with clavulanic acid (AMC) and azithromycin in tonsillitis. Materials and Methods: Prospective, randomized study was carried out in 70 patients of tonsillitis visiting Department of Otorhinolaryngology, Nepal Medical College and Teaching Hospital (NMCTH), Attarkhel, Kathmandu, Nepal. After clinical assessment and recording of baseline sign and symptoms score, patients were randomized into 2 groups. First group received amoxicillin with clavulanic acid and second group received azithromycin. Efficacy of both drugs was compared by reduction in the sign and symptoms score in tonsillitis on 6th day. I.e. after five days of treatment. Results: Both drug groups demonstrated statistically significant reduction in sign and symptoms score after 5 days of treatment when compared from baseline. However, the clinical efficacy of amoxicillin with clavulanic acid and azithromycin did not differ significantly (P>0.05). Conclusion: This study suggests that both the antibiotics, amoxicillin with clavulanic acid and azithromycin had similar efficacy at the end of 5 days treatment. Journal of Universal College of Medical Sciences Vol. 6, No. 1, 2018, page: 22-26